Sensitive determination of malondialdehyde in exhaled breath condensate and biological fluids by capillary electrophoresis with laser induced fluorescence detection - Lačná, Júlia; Foret, František; Kubáň, Petr (Talanta, 2017)
In this work, a sensitive capillary electrophoresis method with laser induced fluorescence detection for determination of malondialdehyde in various biological fluids was developed. Malondialdehyde reacts with thiobarbituric acid under optimized conditions of pH=2, reaction time of 60min and temperature of 90°C, yielding an adduct that can be separated in a 50mM sodium borate background electrolyte at pH 9. The separation of the formed adduct was accomplished in less than 6min with limit of detection of 1.1nM due to the use of 532nm laser module, exactly matching the maximum excitation wavelength of the formed adduct. The developed method offers unprecedented sensitivity and was for the first time used for analysis of malondialdehyde in exhaled breath condensate. The method proved to be also applicable to other samples of biological fluids, such as blood plasma and saliva.
Keywords: Breath Tests; Electrophoresis, Capillary; malondialdehyd; Saliva; sérum; Exhalation; elektroforéza kapilární; Fluorescence; dechové testy; sliny; lidé; vydechnutí; Humans; fluorescence; Lasers; Malondialdehyde; Serum; lasery